PENERAPAN PRINSIP ECO-FISHING PORT DI PELABUHAN PERIKANAN SAMUDERA CILACAP TAHUN 2025 - Annisa Nurul Amalia; Joko Malis Sunarno; Dwi Atin Faidah (Unit Penelitian dan Pengabdian Masyarakat Politeknik Banjarnegara, 2025)
Eco-fishing port is the port management being planned and implemented at several fishing ports in Indonesia. PPS Cilacap is designated by the Ministry of Maritime Affairs and Fisheries to implement this principle, however, there are environmental issues faced by PPS Cilacap, such as sedimentation and waste accumulation in fishing port basin. Therefore, this study was conducted to examine the implementation of the eco-fishing port principle at PPS Cilacap in 2025. This research is a descriptive study with a cross-sectional approach. The sample in this study consisted of 3 people who are part of the eco-fishing port implementation team, the Facilities and Infrastructure Management Team, and the manager of the fish auction site that selected using purposive sampling to gather information regarding waste management, supporting facilities, and hygiene-sanitation of the Fish Auction Place at PPS Cilacap. The result of this study indicate that the variables with the highest score was the environmental management system, waste management system, supporting facilities conditions, and environmental management. The variable with the least score is the sanitation and hygiene condition of the fish auction site. Four assessed parameters were found in good condition, while one parameter still requires improvement. The suggested recommendation includes implementing personal hygiene regulations and providing access cards for TPI visitors, replacing uncovered trash bins with covered ones, and increasing the toilets at fish auction site with separate facilities for men and women to enhance accessibility.